2020
DOI: 10.1111/coa.13510
|View full text |Cite
|
Sign up to set email alerts
|

Interspecialty referral of oesophagogastric and pharyngolaryngeal cancers delays diagnosis and reduces patient survival: A matched case‐control study

Abstract: Objectives: Pharyngolaryngeal and oesophagogastric cancers present with swallowing symptoms and as such, their clinical evaluation traverses boundaries between different specialties. We studied the incidence and significance of interspecialty cancer referrals (ICRs), that is, pharyngolaryngeal cancers first evaluated by gastroenterology and oesophagogastric cancers first evaluated by otolaryngology. Design: A subset analysis of our Integrated Aerodigestive Partnership's audit dataset, of all ICR patients, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Reports of dysphagia in the presence of a normal upper aerodigestive tract examination should prompt urgent esophageal endoscopy to rule out more distal lesions. 26 This study confirmed the finding of a third of cancers on the suspected HNC referral pathway being non‐HNCs and corroborated previous reports. 23 …”
Section: Discussionsupporting
confidence: 92%
“…Reports of dysphagia in the presence of a normal upper aerodigestive tract examination should prompt urgent esophageal endoscopy to rule out more distal lesions. 26 This study confirmed the finding of a third of cancers on the suspected HNC referral pathway being non‐HNCs and corroborated previous reports. 23 …”
Section: Discussionsupporting
confidence: 92%
“…Indeed, previous work on pharyngolaryngeal/esophagogastric malignancies, which often require referrals between head and neck surgery and gastroenterology, has found that interspecialty cancer referrals lead to delays in diagnosis and poorer patient survival. 4 Interestingly, this effect in our study was independent of pathologic lymph node evaluation, suggesting that even cases referred to another surgical specialty for SLNB or elective lymph node dissection receive more timely excision when undergoing MMS. Nevertheless, for cases treated with MMS, pathologic lymph node evaluation was also associated with an increased likelihood of treatment delays.…”
mentioning
confidence: 48%
“…The article by Bird et al is an interesting read and I wish to strongly support their recommendations of a more coherent multidisciplinary approach to dysphagia 1 . UEMS‐ORL are currently in the early stages of forming either an MJC (Multidisciplinary Joint Committee) in Swallowing Disorders or a Thematic Federation in Dysphagia with European colleagues in other relevant specialties, and this publication will certainly assist our endeavours.…”
mentioning
confidence: 85%